2018
DOI: 10.1002/anie.201801173
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Arrangement of Fullerene Acceptors Proximal to Semiconducting Polymers in Mixed Bulk Heterojunctions

Abstract: Precise control of the molecular arrangements at the interface between the electron donor and acceptor in mixed bulk heterojunctions (BHJs) remains challenging, despite the correlation between structural characteristics and efficiency in organic photovoltaics (OPVs). This study reveals that the substitution patterns of linear and branched alkyl side chains on electron-donating/-accepting alternating copolymers can control the positions of an acceptor molecule (C ) around the π-conjugated main chains in mixed B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…The definitions of atom types for PBDB‐T, PC 71 BM, and ITIC are provided in Figure S12, Supporting Information and ref. , and the missing torsion potential parameters for PBDB‐T and ITIC were derived from DFT calculations (Figure S13, Supporting Information and ref. ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The definitions of atom types for PBDB‐T, PC 71 BM, and ITIC are provided in Figure S12, Supporting Information and ref. , and the missing torsion potential parameters for PBDB‐T and ITIC were derived from DFT calculations (Figure S13, Supporting Information and ref. ).…”
Section: Methodsmentioning
confidence: 99%
“…Critical to photovoltaic operation is the donor/acceptor (D/A) interfaces, where photogenerated excitons, namely, Coulombically bounded electron‐hole pairs are dissociated and separated into free charges . Although it is still a challenge to directly probe the heterogeneous, nanoscale, disordered, and buried interfaces at the atomistic level by optical X‐ray and photoelectron techniques, there is a general consensus that tuning the D/A interfaces is essential to maximize exciton dissociation (ED) and minimize charge recombination (CR) for achieving high power conversion efficiencies (PCEs) …”
mentioning
confidence: 99%
“…[13] Chen et al demonstrated that the side chain regiochemistry has a significant influence on the intrinsic aggregation properties of polymer donors, the domain size of blend films, and the performance of the resulting nonfullerene PSCs. [15] The side chain pattern that allows an electron-accepting unit of polymer main chain positioned in close proximity to fullerene produced higher performance in PSC devices. [15] The side chain pattern that allows an electron-accepting unit of polymer main chain positioned in close proximity to fullerene produced higher performance in PSC devices.…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43][44] To further improve the performance of SM OSCs to meet commercial viability, it is highly desirable to unravel what makes the A-π -D-π -A structures special and how to tune the local packing morphology for efficient charge generation by side-chain engineering. These substituents are often detrimental to charge transport and can also influence the donor/acceptor (D/A) intermolecular arrangements.…”
Section: Doi: 101002/adts201800091mentioning
confidence: 99%
“…[41,42,[45][46][47][48][49][50][51][52][53] Nevertheless, faster ED obtained by improving D/A intermolecular interactions are generally accompanied by more severe CR and slower CS. It has been well recognized that the electronic-structure properties of active molecules and D/A complexes at the interfaces are critical to maximize exciton dissociation (ED) and charge separation (CS) and to minimize charge recombination (CR).…”
Section: Doi: 101002/adts201800091mentioning
confidence: 99%